2009
DOI: 10.1152/ajpheart.00496.2008
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial shunt for chronic pulmonary hypertension: differential impact of low-flow vs. high-flow shunting

Abstract: Zierer A, Melby SJ, Voeller RK, Moon MR. Interatrial shunt for chronic pulmonary hypertension: differential impact of low-flow vs. high-flow shunting. Am J Physiol Heart Circ Physiol 296: H639-H644, 2009. First published January 9, 2009 doi:10.1152/ajpheart.00496.2008The purpose of the present study was to determine for the first time the qualitative and quantitative impact of varying degrees of interatrial shunting on right heart dynamics and systemic perfusion in subjects with chronic pulmonary hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Kawaguchi et al reported improved systemic oxygen uptake following interatrial shunting in rats with PHT, but again, the degree of shunting could not be quantified . Our group previously demonstrated in dogs with chronic PHT that low‐flow shunting (15% of CO) could improve RA compliance and CO, whereas high‐flow shunting (29% of CO) reversed those beneficial effects . However, although this controlled shunt model could quantify the shunt flow, it could not determine the crossover point that identifies the shift from the ideal to excess shunting.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Kawaguchi et al reported improved systemic oxygen uptake following interatrial shunting in rats with PHT, but again, the degree of shunting could not be quantified . Our group previously demonstrated in dogs with chronic PHT that low‐flow shunting (15% of CO) could improve RA compliance and CO, whereas high‐flow shunting (29% of CO) reversed those beneficial effects . However, although this controlled shunt model could quantify the shunt flow, it could not determine the crossover point that identifies the shift from the ideal to excess shunting.…”
Section: Discussionmentioning
confidence: 93%
“…Limited studies exist addressing the appropriate degree of shunting that should be produced for different levels of PHT . In 1964, Austen et al found improved hemodynamics and exercise capacity after right‐to‐left shunting in dogs, but their model could not control or quantify the shunt fraction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, Zierer et al [26] had tried to determine the qualitative and quantitative impact of low-flow vs. high-flow shunting. In this study, low-flow shunting (15% of cardiac output) improved RV diastolic compliance by 42% and caused a shift of the RA reservoir-to-conduit ratio toward physiological conditions.…”
Section: Discussionmentioning
confidence: 99%